Pemanfaatan Bahan Alam Dalam Kosmetika Tradisional Dan Keamanannya - Akmal, Yuliandri; Saputra, Indra (Universitas Negeri Jakarta, 2024)
Abstract The use of natural ingredients in cosmetics has become a global trend as public awareness of the importance of environmentally friendly and health-safe products increases. In Indonesia, with its rich biodiversity, traditional cosmetics made from natural ingredients such as aloe vera, turmeric, honey, coconut oil, and bengkuang have strong cultural roots and promising market potential. These ingredients are known for their benefits in skin and body care and minimal side effects. However, challenges remain, including safety risks due to the lack of standard testing, quality variations, and non-compliance with regulations.This study reviews the benefits, safety, and regulations related to the use of natural ingredients in cosmetics. Although natural cosmetics offer a healthier alternative compared to synthetic products, attention to safety testing, product stability, and information transparency is very important. Regulation by supervisory bodies such as BPOM is key to ensuring the quality and safety of traditional cosmetic products. With the right scientific approach and adherence to global standards, natural ingredients in cosmetics can contribute to sustainable product innovation, support the preservation of local culture, and enhance competitiveness in the international market. Keywords: Natural ingredients, traditional cosmetics, cosmetic safety, preservation of local culture